2012
DOI: 10.5897/jcab12.018
|View full text |Cite
|
Sign up to set email alerts
|

Growth curve estimation in pure goat breeds and crosses of first and second generation in Tunisian oases

Abstract: Five non-linear statistical models were tested to fit the growth curve parameters of the kids of indigenous, Alpine and Damascus goats and their crosses. Data from 16 years' periodical weight study was used to adjust the growth curve of 1,687 suckling kids before they attained the age of five months. Among the tested models, the iterative procedure made it possible for the Gompertz model to be identified as the best for use to adjust kids' growth evolution. Brody, Richards, Logistic and Polynomial models showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…They concluded that any of these models can be used for estimating growth curves of Beetal breed. Several studies reported that Gompertz model is an appropriate model for fitting growth curve in goat (Sghaier et al, 2007;Kume and Hajno, T 2011;Gaddour et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that any of these models can be used for estimating growth curves of Beetal breed. Several studies reported that Gompertz model is an appropriate model for fitting growth curve in goat (Sghaier et al, 2007;Kume and Hajno, T 2011;Gaddour et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The growth is explained by Brody, Gompertz, Logistic, Richard's and von Bertalanffy growth models, each of which is defined as a non-linear growth model (Gaddour et al, 2012). These non-linear models are more suitable to describe animal growth because the growth has a sigmoid curve form (Waheed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the non-linear models are more effective than linear models, because of their sigmoid shape [ 36 ]. The Gompertz model is an appropriate model describing the growth in local Tunisian goat kids [ 37 ], Beetal goats [ 25 ], Raeini Cashmere goat [ 38 ], Alpine goat [ 39 , 40 ], local Tunisian goat, and Damascus goats [ 39 ]. Other studies in lambs confirmed the Gompertz model provided the best fit for describing the growth data [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%